2012
DOI: 10.1007/s10967-012-2101-7
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity in coffee

Abstract: This research was dedicated to the study of the background levels of 210Po and natural gamma emitters as 40K, 214Pb, 214Bi, 228Ac, 212Pb and 212Bi in coffee powder and in coffee beverage; also the artificial 137Cs was determined. In the coffee powder the mean 210Po activity resulted 7.25 10-2 ± 2.25 10-2 Bqkg-1. 40K showed a mean activity of 907.4 ± 115.6 Bqkg-1. The mean activity concentration of 214Pb and 214Bi, indicators of 226Ra, given as mean value of the two radionuclides, resulted 10.61 ± 4.02 Bq kg-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…In addition, the 40 K concentration was 46.28% higher in the Turkish coffee than in the Arabian coffee. Moreover, the current results from Arabian and Turkish coffee powders showed a mean concentration of 40 K that was higher than that obtained by Roselli et al (2013), although the mean concentration of 226 Ra was within the range found in the same study. This finding may be linked to contaminated soils in the farming areas (Fatima et al, 2008;Faanu et al, 2016 UNSCEAR (2010), all results fell below the recommended limit for the average exposure rate (84 nGy/h).…”
Section: Average Annual Committed Effective Dose or Dose Ingested By contrasting
confidence: 50%
See 3 more Smart Citations
“…In addition, the 40 K concentration was 46.28% higher in the Turkish coffee than in the Arabian coffee. Moreover, the current results from Arabian and Turkish coffee powders showed a mean concentration of 40 K that was higher than that obtained by Roselli et al (2013), although the mean concentration of 226 Ra was within the range found in the same study. This finding may be linked to contaminated soils in the farming areas (Fatima et al, 2008;Faanu et al, 2016 UNSCEAR (2010), all results fell below the recommended limit for the average exposure rate (84 nGy/h).…”
Section: Average Annual Committed Effective Dose or Dose Ingested By contrasting
confidence: 50%
“…Coffee is one of the most popular and widely consumed beverages in the world, and its consumption is increasing (Roselli et al, 2013). However, variation exists in the annual consumption between countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although its chemical composition includes nutritional compounds, some with bioactive activity, the World Health Organization (WHO) defines coffee as "a non-dietary component" 116 ; however, it is considered the primary source of dietary antioxidants in industrialized countries (eg, ~ 66% in Brazil, ~ 64% in Norway, ~ 45% in Spain, ~ 56% in Japan) 1,34,49,84,[117][118][119][120] and it is estimated that the daily consumption of 4 to 5 cups of coffee covers ~ 64 to 66% of the antioxidant dietary requirements. 69,121 It can be speculated that the chemo-protective effects of coffee are partly due to its ability to intracellularly neutralize oxidizing agents such as free radicals, many of which are positively charged molecules (eg, NO + , NO -, ONOO -, H 2 O 2 , O 2 -, NO, & OH -) in search of electrons to stabilize.…”
Section: Discussionmentioning
confidence: 99%